Recombinant Expression and Immobilization of Pantoea dispersa DJL-B Alcohol Dehydrogenase - Hong TIAN; Li PANG; Wentao YANG; Xiao CHEN; Jinghan WANG; Bo XIA; Liwen JIANG (Shipin gongye ke-ji)
To enhance the expression level of recombinant alcohol dehydrogenase in E. coli BL21 (DE3), this study investigated the effects of induction temperature, induction time, and IPTG concentration on enzyme expression through one-way experiments. Additionally, the immobilization of recombinant alcohol dehydrogenase using sodium alginate embedding was examined to improve its application in geraniol conversion. The results indicated that the optimal expression conditions for recombinant alcohol dehydrogenase in E. coli BL21 (DE3) were an induction temperature of 28 ℃, an induction time of 20 hours, and an IPTG concentration of 0.1 mmol/L. Furthermore, the conditions for immobilization were: immobilization temperature of 20 ℃, sodium alginate concentration of 3.5%, and enzyme addition of 500 μL. Meanwhile, the immobilized enzyme showed good mechanical stability, and the relative enzyme activity was still maintained at about 60% after 5 times of reuse, demonstrating good reusability. The results of the study provide an important theoretical reference for the industrial preparation of geranial using immobilized enzyme catalysis, which has good application prospects.